Avaliação da estrutura e processo assistencial de enfermagem na prevenção e controle da infecção de sítio cirúrgico em pacientes submetidas à cirurgia oncológica de mama - Silva, Lúcia Marta Giunta da [UNIFESP] (2009)
Introduction: High rates of infection can reflect low health service quality. The fact that previous studies performed at the same location of the present study found surgical site infection rates (SSI) ranging from 14.1% to 22% raised questions about the possibility of the nursing care structure and process to affect those rates. After obtaining this first answer, another question emerged, concerning the capacity of an inservice training program be able to encourage the participants, by means of an interactive dynamics, to develop proposals or projects from making changes. Objectives: To evaluate nursing care structure and process in preventing and managing SSI; and evaluate an inservice training program for nurses involved in the context of the identified problems, using interactive educational strategies aiming at the prevention and control of this complication. Method: This intervention study was approved by the UNIFESP Research Ethics Committee under register 1486/07, and was developed in two stages. The first stage consisted of and observation and analysis study, performed by means of inspections of the structure and process at the Gynecology Oncomastology Units at Hospital São Paulo (HSP), between August 2007 and March 2008. This stage was described in the first article that composes this dissertation. The second stage used a quali-quantitative approach and was performed from October 2008 to September 2009. It consisted of the structure, development, and evaluation of the educational project in a virtual environment for the Training Program at Work for nurses of the referred hospital units, in SSI control, based on the Skopos Model, and organized based on the resources of the Moodle environment. The data regarding this stage was described in the three subsequent articles that comprise the dissertation. Results: The evaluation of the nursing care structure and process showed that the normative document were in agreement with the literature; however, the physical structure and the nursing care processes of the studied locations presented important limitations, which had a negative impact on the development of adequate health care processes to prevent SSI. In terms of the structure and use of a virtual learning environment in continuing nursing education, Moodle showed to be valuable in structuring a nursing training program, which sought to stand apart from a unilateral and hierarchical communication model. The evaluation of goal achievement and content adequacy of the referred program was performed by four nurses who participated in the process. The nurses found that the program presents clear benefits and the main limiting factors associated with inservice training. In addition, although new educational strategies, particularly if interactive, are welcome, the professionals preferred in-person meetings. Finally, using the HFMEA® and the Ishikawa diagram permitted to analyze four nursing care processes and their forms of failure: 1) scheduling a surgery through the Oncomastology Unit; 2) Surgery Patient Admission and Discharge Flow at the Gynecology Hospitalization Unit; 3) Performing Outpatient Surgical Procedures; 4) Outpatient Return Appointments for Surgery Patients. In addition, it was possible to make a list of improvement actions that were initiated based on the discussions held during the training program. Conclusions: The study results evidenced the need to review the nursing care process and to make the structure adequate with a view to meet the standards for SSI prevention and control. As for the inservice training program, the experience of using educational technology at the referred institution was feasible and provided the chance for group analyses about the problematic situation, as well as the proposal of actions for its solution. However, just as any innovative process, there is a pathway to be constructed so that nurses, who are used to training programs that are expositive, performed on-site and focused on previously determined objectives become capable of benefiting from interactive, collaborative, and project-based strategies.